2015
DOI: 10.1111/imm.12505
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T‐cell priming upon mRNA vaccination is restricted to bone‐marrow‐derived antigen‐presenting cells and may involve antigen transfer from myocytes

Abstract: SummarySelf-amplifying mRNAs (SAM ® ) are a novel class of nucleic acid vaccines, delivered by a non-viral delivery system. They are effective at eliciting potent and protective immune responses and are being developed as a platform technology with potential to be used for a broad range of targets. However, their mechanism of action has not been fully elucidated. To date, no evidence of in vivo transduction of professional antigen-presenting cells (APCs) by SAM vector has been reported, while the antigen expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 57 publications
0
49
0
1
Order By: Relevance
“…RNAs were formulated with LNPs as previously described [ 34 ] and diluted to the desired RNA concentration (1 ng/μl) with PBS. For the SAM(NP)+SAM(M1) formulation, an equal amount of SAM(NP) and SAM(M1) RNAs was mixed prior to complexion with LNP.…”
Section: Methodsmentioning
confidence: 99%
“…RNAs were formulated with LNPs as previously described [ 34 ] and diluted to the desired RNA concentration (1 ng/μl) with PBS. For the SAM(NP)+SAM(M1) formulation, an equal amount of SAM(NP) and SAM(M1) RNAs was mixed prior to complexion with LNP.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the immunostimulation was limited to the injection site and lymphoid organs as no proinflammatory cytokines were detected in the serum of the immunized mice. Lazzaro et al demonstrated that CD8 + T-cell priming is restricted to bone-marrow-derived APCs and may involve antigen transfer from myocytes suggesting cross-priming as the prevalent mechanism upon IM injection of self-amplifying mRNA vaccines in mice ( 166 ). In a recent publication, Lutz et al provided first mechanistic insights into the mode of action of LNP-formulated non-replicating sequence optimized mRNA vaccines, demonstrating a strong activation of the innate immune response at the injection site and in the dLNs in mice.…”
Section: Vaccine Technologiesmentioning
confidence: 99%
“…After intramuscular application, transfected myocytes may undergo apoptosis. Apoptotic bodies are engulfed by APC and the exogenous antigen is cross-presented on MHCI resulting in a CD8 + T cell response [ 17 ]. Early studies on DNA vaccination demonstrated that priming of CD8 + cytotoxic T lymphocytes (CTL) is mostly dependent on bone marrow-derived DC rather than induced by tissue specific cells [ 18 ], and was strictly dependent on CD4 + T cell help [ 19 ].…”
Section: Course Of Action Of Dna Vaccinesmentioning
confidence: 99%